An analysis of SmBa0.5Sr0.5Co2O5+δ double perovskite oxide for intermediate–temperature solid oxide fuel cells - Subardi, Adi; Susanto, Iwan; Kartikasari, Ratna; Tugino, Tugino; Kuntara, Hasta; Wijaya, Andy Erwin; Purnomo, Muhamad Jalu; Indra, Ade; Fahmi, Hendriwan; Fu, Yen-Pei (Eastern-European Journal of Enterprise Technologies, 2021)
The main obstacle to solid oxide fuel cells (SOFCs) implementation is the high operating temperature in the range of 800–1,000 °C so that it has an impact on high costs. SOFCs work at high temperatures causing rapid breakdown between layers (anode, electrolyte, and cathode) because they have different thermal expansion. The study focused on reducing the operating temperature in the medium temperature range. SmBa0.5Sr0.5Co2O5+δ (SBSC) oxide was studied as a cathode material for IT-SOFCs based on Ce0.8Sm0.2O1.9 (SDC) electrolyte. The SBSC powder was prepared using the solid-state reaction method with repeated ball-milling and calcining. Alumina grinding balls are used because they have a high hardness to crush and smooth the powder of SOFC material. The specimens were then tested as cathode material for SOFC at intermediate temperature (600–800 °C) using X-ray powder diffraction (XRD), thermogravimetric analysis (TGA), electrochemical, and scanning electron microscopy (SEM) tests. The X-ray powder diffraction (XRD) pattern of SBSC powder can be indexed to a tetragonal space group (P4/mmm). The overall change in mass of the SBSC powder is 8 % at a temperature range of 125–800 °C. A sample of SBSC powder showed a high oxygen content (5+δ) that reached 5.92 and 5.41 at temperatures of 200 °C and 800 °C, respectively. High diffusion levels and increased surface activity of oxygen reduction reactions (ORRs) can be affected by high oxygen content (5+δ). The polarization resistance (Rp) of samples sintered at 1000 °C is 4.02 Ωcm2 at 600 °C, 1.04 Ωcm2 at 700 °C, and 0.42 Ωcm2 at 800 °C. The power density of the SBSC cathode is 336.1, 387.3, and 357.4 mW/cm2 at temperatures of 625 °C, 650 °C, and 675 °C, respectively. The SBSC demonstrates as a prospective cathode material for IT-SOFC